EVALUATION OF THE ANTIFUNGAL SUSCEPTIBILITY AND KARYOTYPE OF Cryptococcus neoformans ISOLATED FROM CLINICAL SAMPLES IN VENEZUELA - B Calvo; A Colombo; O Fischman; A Santiago; F Nunes; Branchini, M.L Branchini (Kasmera, 2000)
Thirty (30) samples coming from 27 HIV infected and non-infected patients were studied to assess antimicotic susceptibility and karyotype of Cryptococcus neoformans clinical isolates obtained in Venezuela. Identification of each sample was performed by standard methods, variety classification was based on growth in CGB agar medium, serotyping was performed by slide agglutination with five specific sera. Antifungal susceptibility was performed for amphothericin B, fluconazole, itroconazole and 5-flucytosine, according to NCCLS recommendations and karyotype study was done through contour clamped homogenous field gel electrophoresis (CHEF). Twenty seven (27) isolates of C. neoformans var. neoformans were obtained,all being of serotype A, and three (3) isolates of C. neoformans var. gattii, two (2) belonging to serotype B and one (1) to serotype C. Strains of this series were highly susceptible to the antifungal agents tested. Electrophoretic Karyotype (EK) analysis showed 13 profiles, presenting between 7 and 9 chromosomes and the molecular weight variation was 450/565 and 2200 kb. No significant differences were observed between the minimum inhibitory concentrations (MIC), nor was it possible to associate EK profiles among the isolates of HIV and non HIV patients. Further clinical and laboralorial investigations are mandatory to improve the understanding of C. neoformans in Venezuela.